PERANCANGAN APLIKASI WEB UNTUK PENCARIAN LOKASI DAN RUTE RUMAH SAKIT BERBASIS GOOGLE MAPS API - Daniel Oktodeli Sihombing (Universitas Bina Sarana Informatika, 2015)
Future information needs now fundamental to social life. The information provided in the present is in need of maximized by transforming data into visual form with aspects of other support so that the data can be processed into information for those who need it. Coordinate point is an important part of the mapping coordinates of the point where it becomes the initial data where an object is located. Hospital physical position we can know the location and its place in the data but sometimes it becomes abstract proficiency level so that the system is not able to optimally display information about the location of the hospital. Existing hospital in the city of Pontianak spread evenly. This distribution will be an issue in determining the route to the hospital if in an emergency. Based on these problems in this study aims to how to produce a web-based application that can be used to find the location of the hospital as well as how to obtain information about the route followed to get to the hospital. Web application designed to display information about the hospital in the town of Pontianak and convert latitude and longitude coordinates of the hospital to digital maps using Google Maps API as well as showing the way to the hospital by using the Google Directions API.Keywords: Google Maps API, Google Directions API, Pencarian, Rute Rumah Sakit